Kontribusi Regulasi Diri terhadap Perilaku Cyberloafing pada Tenaga Kesehatan di Puskesmas Kecamatan X - Lasmi Dwi Tri Deani; Mario Pratama (Jurnal Pengabdian Ilmu Kesehatan, 2025)
This study aims to analyze the contribution of self-regulation to cyberloafing behavior among healthcare workers at the X Sub-District Community Health Center (Puskesmas). The research background is driven by the widespread internet usage in Indonesia, reaching 229 million users or 80.66% penetration rate in 2025 (APJII, 2025), which potentially leads to digital distractions such as cyberloafing that disrupt productivity and patient safety in the healthcare sector. A quantitative regression approach was employed with a sample of 104 respondents, utilizing the Self-Regulation Questionnaire adapted from Pichardo et al. (2014) (15 items, 1-4 scale) and the Cyberloafing Scale from Blanchard and Henle (2008) (8 items, 1-5 scale). Data were analyzed using simple linear regression via IBM SPSS version 26.0. The results indicate that self-regulation has a significant negative effect on cyberloafing (t = -12.042, p < 0.05; β = -0.621), contributing 58.7% (R² = 0.587). These findings suggest that enhancing self-regulation can suppress cyberloafing tendencies, recommending daily training programs and restricted internet access policies at puskesmas to improve service responsiveness.